Transmembrane signaling in human polymorphonuclear neutrophils: 15(S)-hydroxy-(5Z,8Z,11Z,13E)-eicosatetraenoic acid modulates receptor agonist-triggered cell activation. - Smith, R J (1993)
15(S)-Hydroxy-(5Z,8Z,11Z,13E)-eicosatetraenoic acid (15-HETE) exerted a time- and concentration-dependent inhibition of superoxide anion (O2-) production and exocytosis of both azurophil and specific granule constituents from human polymorphonuclear neutrophils (PMN) stimulated with the receptor-specific agonists, N-formylmethionylleucylphenylalanine (FMLP), platelet-activating factor, and leukotriene B4, but not that elicited by phorbol 12-myristate 13-acetate. 15-HETE did not alter the binding of FMLP to its specific receptors on PMN but, rather, appeared to interfere with a subsequent process in signal transduction. Receptor-coupled production of inositol 1,4,5-trisphosphate (InsP3) and increases in cytosolic free calcium elicited with FMLP, platelet-activating factor, and leukotriene B4 were suppressed by 15-HETE. 15-HETE did not, however, inhibit the mobilization of 45Ca from intracellular stores elicited by the addition of InsP3 to permeabilized PMN. 15-HETE suppressed O2- production and increases in intracellular [Ca2+] induced when cell-surface receptors were bypassed and the PMN were activated directly by the guanine nucleotide-binding protein (G protein) activators aluminum fluoride (AlF4-) and mastoparan. 15-HETE, however, did not perturb all G protein functions because cAMP production in FMLP-activated PMN was essentially unaffected by 15-HETE. These data support the proposition that 15-HETE modulates receptor-triggered activation of PMN either by uncoupling G protein stimulation of phospholipase C or by directly inhibiting phospholipase C, thus inhibiting the InsP3-dependent rise in intracellular [Ca2+] that is prerequisite for PMN responsiveness to receptor agonists.